Evolusi Sasando: Perubahan Alat Musik Tradisional Menuju Era Elektrifikasi - Muhammad Hafidz Aditya Ramadhan; Syairul Bahar; Rizky Susanto; Salsabila Hanum; Sya Mandhalaksita Irsani (Publikasi Inspirasi Indonesia, 2023)
East Nusa Tenggara (NTT) as a province with a wealth of traditional arts and culture, maintains this heritage in a form that remains authentic and has undergone transformation. This article reviews the history and transformation of sasando, a typical musical instrument of NTT, to understand the dynamics of change in traditional arts as sasando evolves. This research adopts a qualitative method by interviewing NTT natives in Taman Mini Indonesia Indah, and utilising a literature review. The electric sasando, born from Arnoldus Edon's innovation in 1960, is the main focus of the discussion. As technology develops, the design and sound quality of the electric sasando continues to be updated. Despite this recognition, different views emerged among art connoisseurs. The electric sasando is considered practical and compatible with modern music by some, while others feel that its sound character has changed, losing the uniqueness of the traditional sasando. Comparisons between the two are considered irrelevant, as both have their own uniqueness. In conclusion, the changes in sasando reflect the dynamics of popular culture, which should be accepted with a critical attitude.